Aplikasi Hidroksiapatit Sebagai Bone Filler Pasca Pencabutan Gigi - Rahmawati, Dyah; Sunarso, Sunarso; Irawan, Bambang (Jurnal Material Kedokteran Gigi; Vol 9 No 2 (2020): JMKG Vol 9 No 2 September 2020, 2021)
Trauma arising from tooth extraction will experience a natural healing process but alveolar defects will only partially heal. Along with bone growth, there is also a resorption process in the alveolar ridge. Socket preservation with bone graft can be a solution to maintain ridge dimensions and contours so that bone resorption can be minimized. Hydroxyapatite is a synthetic biomaterial that repairs damage after tooth extraction and regenerates bone associated with implant placement and denture bases as a replacement procedure for missing teeth. This paper was created to discuss the role of Hydroxyapatite (HA) as bone filler after tooth extraction. Socket preservation or preservation of the socket or alveolar ridge preservation is a procedure performed to reduce the process of bone loss after tooth extraction. This loss of bone volume may result in the denture becoming loose, or an insufficient amount of bone width to place the implant. Hydroxyapatite (HA) is an alloplastic material commonly used as a replacement for bone grafts due to its inherent bioactive properties that support osteoconduction . HA is a synthetic biomaterial that can repair damage after tooth extraction and regenerate bone associated with missing tooth replacement procedures.